PELAKSANAAN PERJANJIAN FRANCHISE BEBEK PAK NDUT DI KOTA SAMARINDA MENURUT HUKUM PERDATA - Ekawati, Ekawati (LEGALITAS : Jurnal Ilmiah Ilmu Hukum, 2019)
Franchise business is a future business trend with a small risk of failure where growth is very rapid and gives its own color in the Indonesian economy. Franchise agreement is one aspect of legal protection to the parties from acts that harm other parties. If one party violates the contents of the franchise agreement, then the other party can sue the infringing party in accordance with applicable law. Franchising in Indonesia is currently regulated in Government Regulation No. 42/2007 concerning Franchising. In PP No.42 of 2007 it also stipulates that a contract must be made clearly. And if we observe that currently in Indonesia there are already many franchise businesses in the field of food that are very creative. The Pak Ndut Duck franchise is a franchise agreement for the sale of Pak Ndut's chicken and duck food products. As a result of the existence of a product sales franchise agreement, the parties are bound in a right and obligation. This type of research is analytical descriptive, namely to describe, discover legal facts as a whole and systematically study the Implementation of the Pak Ndut Duck Franchise Agreement in Samarinda City. The parties involved in the fanchise agreement (franchise) are explained in Article 1 paragraph (2) and (3) Republic of Indonesia Government Regulation No. 42 of 2007 concerning Franchises states that the franchisor (Franchisor) is an individual or business entity that gives the right to use or use the franchise he owns to the franchisee.